Challenges facing the ministerial formation in Uniting Presbyterian Church in Southern Africa: A critical reflection - Mogashoa, Moroka (HTS teologiese studies, 2017)
Following the union of the Presbyterian Church of Southern Africa (PCSA) and Reformed Presbyterian Church in Southern Africa (RPCSA) to form the Uniting Presbyterian Church in Southern Africa (UPCSA) in 1999, it was necessary to consolidate theological education of a united church. This was a wise and bold decision by UPCSA, as a first attempt to integrate the training of both black and white students, but more importantly to give institutional expression to the advancement of unity. University of Pretoria (UP) became a major training centre of the UPCSA. Collaboration in ministerial formation between UPCSA and UP, its partner institution, has been plagued by manifold challenges. The challenges which will come under the spotlight are ecumenism, relationship between the university and the UPCSA, curriculum and spirituality.